HUBUNGAN CARA BELAJAR DAN KONDISI EKSTERNAL BELAJAR DENGAN HASIL BELAJAR PADA MATA PELAJARAN EKONOMI SISWA KELAS XI IPS - Nur Hasanatul Azizah; Mardono Mardono; Agung Haryono (Jurnal Pendidikan Ekonomi, 2015)
Correlational descriptive study aimed to elaborate on the relationship between the variables in the study. The variable in this study is a way of learning (X1), the external conditions of learning (X2), and the learning outcomes (Y). Subjects numbered 72 students MA AL-AZIZ Dampit District of Malang. The survey results revealed that there is a relationship between learning with learning outcomes on economic subjects, and there is a relationship between the external conditions of learning with learning outcomes on economic subjects.